2022
DOI: 10.1080/19490976.2022.2029674
|View full text |Cite
|
Sign up to set email alerts
|

Circulating microbiome in patients with portal hypertension

Abstract: Portal hypertension (PH) in liver cirrhosis leads to increased gut permeability and the translocation of bacteria across the gut–liver axis. Microbial DNA has recently been detected in different blood compartments; however, this phenomenon has not been thoroughly analyzed in PH. This study aimed to explore circulating bacterial DNA signatures, inflammatory cytokines, and gut permeability markers in different blood compartments (peripheral and hepatic veins) of patients with cirrhosis and PH. The 16S rRNA blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 70 publications
(75 reference statements)
1
32
0
Order By: Relevance
“…In addition, the increased abundance of certain tumour-promoting bacteria, such as Neisseria, and the low infiltration of antitumour bacteria, such as Pseudomonas , may further influence HCC progression [ 36 , 37 ]. The research conducted by Rolandas Gedgaudas et al proved that intestinal permeability in patients with portal hypertension was significantly higher than that in the healthy control group, which was accompanied by a high abundance of some bacteria in peripheral blood [ 38 ]. These bacteria mainly included Enterobacteriaceae, Shigella and many other kinds of bacteria, which is consistent with the high abundance of bacteria in HCC tissues observed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the increased abundance of certain tumour-promoting bacteria, such as Neisseria, and the low infiltration of antitumour bacteria, such as Pseudomonas , may further influence HCC progression [ 36 , 37 ]. The research conducted by Rolandas Gedgaudas et al proved that intestinal permeability in patients with portal hypertension was significantly higher than that in the healthy control group, which was accompanied by a high abundance of some bacteria in peripheral blood [ 38 ]. These bacteria mainly included Enterobacteriaceae, Shigella and many other kinds of bacteria, which is consistent with the high abundance of bacteria in HCC tissues observed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The strongest relationships with IL-8 were found in Escherichia coli and Prevotella . This could be due to these bacteria’s propensity to produce LPS and cause inflammation via TLR or inflammasome cascades ( Gedgaudas et al., 2022 ). Proteobacteria also produce LPS which has a direct role in cardiovascular diseases, it may suggest that phylum Proteobacteria and genus Escherichia-Shigella might play a potential role in chronic coronary syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…The changes and shifts of intestinal flora caused by cirrhosis and portal hypertension had always been a research hotspot, but this phenomenon had not been thoroughly analyzed in PH. A recent study from 2022 ( 47 ) has shown that the circulating plasma microbiota profile of cirrhotic patients was significantly different from that of the control group, characterized by rich Comamonas , Cnuella, Dialister , Escherichia/Shigella , and Prevotella , but poor Bradyrhizobium , Curvibacter , Diaphorobacter , Pseudarcicella , and Pseudomonas . There was no significant difference in peripheral and hepatic venous blood in patients with cirrhosis.…”
Section: Discussionmentioning
confidence: 99%